Pengaruh Kekuasaan Atas Pengetahuan (Memahami Teori Relasi Kuasa Michel Foucault) - Arif Syafiuddin (Refleksi: Jurnal Filsafat dan Pemikiran Keislaman, 2018)
This article attempts to outline the concept of power of Michel Foucault based on the major works that he wrote during his lifetime. Foucault asserts that power exists everywhere, especially concerning the relationship between power and discourse of knowledge. Here, for him, the will to truth is the expression of the will to power. It is impossible for the knowledge to be neutral and pure. Therefore, there will be always a correlation between the two matters, i.e. the knowledge contains power, just like the power contains knowledge. This means that power is one dimension of the relation. Where there is a relationship, there is a power.